Development of Creativity-Based Physics Lab Equipment: A New Solution for Deep Concept Understanding - Wattimena, Herman Semuel (Pascasarjana, Mataram University, 2025)
This study aims to produce physics learning devices that can be used by students in carrying out physics practical activities in high school; so that their conceptual understanding of physics can be improved, as well as being able to increase their creativity in physics practical activities. Data collection was carried out through observation, questionnaires, interviews, and tests. Data analysis was processed qualitatively and quantitatively. Qualitative data processing was carried out through transcription, tabulation, coding, description, and analysis. Quantitative data was processed using N-gain based on pretest data and posttest data for the experimental and control classes. The effectiveness of the developed learning devices can be seen through the results of expert analysis and quantitative analysis of test results. The results of the study based on N-gain analysis showed thatThe developed high school physics learning device appears to be able to improve students' conceptual understanding and improve their creative thinking skills in experimenting by 0.49 in the moderate category